The English Use of Indonesian Students in Australia: Expectations, Perceptions, and Strategies - Lazuar Azmi Zulferdi (Journal of Foreign Language Teaching and Learning, 2021)
This paper explores the use of English in Australia based on the perspectives of Indonesian students. Studies on perception, expectations, and strategies on social experience have been carried out. However, most of these studies have not established models that consider the relationship among the three elements of expectations, perceptions, and strategies of Indonesian students in the host country, particularly in Australia. This paper attempts to capture the holistic picture of English varieties in the Australian higher education context to draw upon the three elements. Demographic questionnaire surveys and semi-structured interviews were employed to obtain data from fifteen Indonesian students studying in three universities in Melbourne, Australia. This paper's findings suggested that Indonesian students' expectations, perceptions, and strategies varied due to limited awareness regarding English varieties, culture gaps between Australia and Indonesia, and the prominent role of individual self-reflection. It is hoped that this paper may shed light on people’s understanding of the challenges, experiences, and the general wellbeing of international students who choose to study in Australia for their tertiary education.